2023
DOI: 10.3389/fmolb.2023.1130625
|View full text |Cite
|
Sign up to set email alerts
|

DPP-4 inhibitors for treating T2DM - hype or hope? an analysis based on the current literature

Abstract: DPP-4 inhibition is an interesting line of therapy for treating Type 2 Diabetes Mellitus (T2DM) and is based on promoting the incretin effect. Here, the authors have presented a brief appraisal of DPP-4 inhibitors, their modes of action, and the clinical efficiency of currently available drugs based on DPP-4 inhibitors. The safety profiles as well as future directions including their potential application in improving COVID-19 patient outcomes have also been discussed in detail. This review also highlights the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 192 publications
(234 reference statements)
1
14
0
Order By: Relevance
“…Also, they reduce body weight and blood pressure, showing the potential to slow the progression of diabetes and reduce the cardiovascular complications of diabetes. [8,9] Thus, incretin-based drugs have likewise received some attention for their association with PCa risk. [10] Several basic studies have shown that incretin-based drugs can inhibit the growth of prostate cancer cells in in vitro assays.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they reduce body weight and blood pressure, showing the potential to slow the progression of diabetes and reduce the cardiovascular complications of diabetes. [8,9] Thus, incretin-based drugs have likewise received some attention for their association with PCa risk. [10] Several basic studies have shown that incretin-based drugs can inhibit the growth of prostate cancer cells in in vitro assays.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the concept of tight-binding inhibitors emerges as pivotal in the pharmacological context. The ability of these inhibitors to tightly bind to their target ensures a sustained inhibition of enzyme activity, 9 which results in persistent diurnal effects on glucose, β cells and incretin hormones without significant differences between them. 9 , 10 …”
Section: Introductionmentioning
confidence: 99%
“…They also have other beneficial effects on glucose metabolism, lipid metabolism, appetite regulation, gut motility, and immune function. They also have anti-inflammatory properties that reduce cardiovascular risk, help preserve beta-cell function, and improve renal function [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the common side effects of DPP-4 inhibitors are upper respiratory tract infections, urinary tract infections, headaches, and nasopharyngitis. Moreover, this class of drugs has been associated with rare but serious complications, such as pancreatitis, pancreatic cancer, thyroid cancer, and sometimes severe allergic reactions [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%